Recent advances toward a molecular mechanism of efflux pump inhibition - Opperman, Timothy J.; Nguyen, Son T. (Frontiers in Microbiology, 2015)
Multi-drug resistance (MDR) in Gram-negative pathogens, such as the Enterobacteriaceae and Pseudomonas aeruginosa, poses a significant threat to our ability to effectively treat infections caused by these organisms. A major component in the development of the MDR phenotype in Gram-negative bacteria is overexpression of RND-type efflux pumps, which actively pump antibacterial agents and biocides from the periplasm to the outside of the cell. Consequently, bacterial efflux pumps are an important target for developing novel antibacterial treatments. Potent efflux pump inhibitors (EPIs) could be used as adjuvant therapies that would increase the potency of existing antibiotics and decrease the emergence of MDR bacteria. Several potent inhibitors of RND type efflux pump have been reported in the literature, and at least three of these EPI series were optimized in a pre-clinical development program. However, none of these compounds have been tested in the clinic. One of the major hurdles to the development of EPIs has been the lack of biochemical, computational, and structural methods that could be used to guide rational drug design. Here we review recent reports that have advanced our understanding of the mechanism of action of several potent EPIs against RND-type pumps.